White‐tailed deer fawn recruitment before and after experimental coyote removals in central Georgia - William D. Gulsby; Charlie H. Killmaster; John W. Bowers; James D. Kelly; Benjamin N. Sacks; Mark J. Statham; Karl V. Miller (Wildlife Society Bulletin)
ABSTRACT Recent evidence from across the southeastern United States indicating high predation rates by coyotes (Canis latrans) on white‐tailed deer (Odocoileus virginianus) fawns has led some managers to implement coyote control. Although some evidence suggests coyote control can improve recruitment, success appears to be site dependent. Therefore, we designed an experiment to assess feasibility of coyote control as a management action to increase recruitment on B.F. Grant and Cedar Creek Wildlife Management Areas (WMA) in central Georgia, USA. We estimated annual coyote abundance during 2010–2012 using a noninvasive mark–recapture design and fawn recruitment using infrared‐triggered camera surveys. During March–June 2011 and March–April 2012, trappers removed coyotes from both sites. Estimates of coyote abundance on B.F. Grant WMA after trapping were 81% (2011) and 24% (2012) lower than during preremoval. Coyote abundance estimates were similar among years on Cedar Creek WMA. Fawn recruitment on B.F. Grant WMA averaged 0.65 fawns/adult female prior to removal and 1.01 fawns/adult female during the 2 years following the removals. Fawn recruitment on Cedar Creek WMA did not differ among years during the study, and was similar to that prior to coyote arrival. The differential coyote impacts and variable effectiveness of trapping we observed on nearby sites suggest coyote control may not achieve management objectives in some areas. Furthermore, transient behavior and the potential for coyotes to adapt to control efforts likely reduce efficacy of this management action. However, we observed an increase in recruitment on B.F. Grant WMA during one year, and others have seen similar responses. Therefore if lowered fawn recruitment is hindering achievement of management objectives, we recommend managers who opt to control coyotes continuously monitor recruitment to determine whether a response occurs. © 2015 The Wildlife Society.